Digital measurement method for comparing the absolute marginal discrepancy of three-unit ceramic fixed dental prostheses fabricated using conventional and digital technologies - Shanshan Liang; Fusong Yuan; Deli Li; Lu Jia; Yuchun Sun (BMC, 2023)
Abstract Background In clinical practice, control of the marginal fit of fixed dental prostheses is hindered by evaluation method, which needs to be further improved to increase its clinical applicability. This study aimed to quantitatively analyze the absolute marginal discrepancy of three-unit ceramic fixed dental prostheses fabricated by conventional and digital technologies using a digital measurement method based on the digital impression technology and open source software. Methods A digital workflow and the conventional impression combined with the lost-wax heat-pressed technique were adopted to separately fabricate 10 glass ceramic fixed dental prostheses. Three-dimensional data for the abutments, fixed dental prostheses, and fixed dental prostheses seated on the abutments, were obtained using a dental scanner. The two datasets were aligned using registration technology, specifically "multi-points registration" and "best fit alignment," by reverse engineering software. Subsequently, the three-dimensional seated fit between the fixed dental prostheses and abutments were reconstructed. The margin of the abutment and crown was extracted using edge-sharpening and other functional modules, and the absolute marginal discrepancy was measured by the distance between the margin of the abutment and crown. One-way analysis of variance was used to statistically analyze the measurement results. Results Using the digital measurement method, the mean value of absolute marginal discrepancy for fixed dental prostheses fabricated by the conventional method was 106.69 ± 6.46 μm, and that fabricated by the digital workflow was 102.55 ± 6.96 μm. The difference in the absolute marginal discrepancy of three-unit all-ceramic fixed dental prostheses fabricated using the two methods was not statistically significant (p > 0.05). Conclusions The digital measurement method for absolute marginal discrepancy was preliminarily established based on open source software and applied in three-unit ceramic fixed dental prostheses. The absolute marginal discrepancy of three-unit ceramic fixed dental prostheses fabricated using digital technology was comparable to that of conventional technique.